Analysis of Revenue Receipt and Methods for Recording Service Income - Dewi, Siti Ratna Sari; Rizkia, Nita Putri (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This research uses a combined method of observation and interviews to analyze income receipts and methods for recording service income at PT. Auto Jaya Tekno during the 2016-2018 period. Observations were carried out directly on the research object by participating in interactions in the PT's natural environment. Auto Jaya Tekno. Interviews were conducted with op-erational division area managers related to the research to obtain in-depth in-formation regarding the revenue receipt process and methods for recording service revenue. Data collection instruments involve interview and observa-tion guidelines, as well as special formats in tables and forms.Data analysis uses descriptive techniques, utilizing the results of inter-views and observations. Data is constructed to provide an in-depth under-standing of the problem being studied; then, the results are compared with relevant theories. The research results show that PT. Auto Jaya Tekno has successfully implemented the SOP for recording income and costs with con-sistency using the accrual basis method in accordance with PSAK No. 23. Using the Limax system provides the advantage of automatic and simultaneous recording of transactions. The company also continues to implement a credit sales policy by paying attention to the risk of bad debts. Thus, this re-search provides an in-depth overview of revenue receipts and methods of recording service revenue at PT. Auto Jaya Tekno, which can be a founda-tion for companies for efficient and accountable financial management.